(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In our study, Antalya has a 25% em.k. 0.015%, Luna Ekspiriens 40% sus.k against flour dew disease, which occurs in apple orchards grown intensively. 0.1% li, Serkadis Plus 125 g/l sus.k. 0.1% and Scorart 25% em.k. When using 0.02% fungicides, the damage ranged from 6.0% to 6.5% in the leaves, from 4.1% to 4.5% in the fruits, the disease progressed from 2.2% to 2.8% and 1, respectively. Biological efficiency ranged from 87,9% to 90,6% in leaves and from 90,9% to 91,6% in fruits, from 2% to 1,3%.